The prevalence of infertility in 20-49 years women in Yazd, 2014-2015: A cross-sectional study - Masoud Mirzaei; Nasim Namiranian; Razieh Dehghani Firouzabadi; Somaye Gholami (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Infertility is a serious health problem that affects the individual, her/his family, and the community. Infertility is defined as failure to achieve clinical pregnancy after at least 12 months of unprotected coitus. Objective: The purpose of this study was to investigate the prevalence of primary and secondary infertility and the associated factors in Yazd Greater Area during 2014-2015. Materials and Methods: This is a cross-sectional analytic study using Yazd Health Study data which was conducted on 10,000 people. We studied 2611 women between 20-49 yr old who lived in Yazd Greater Area. Data were collected using a validated questionnaire. Anthropometrics were collected using standardized instruments. Results: Among women participating in the study, 135 cases of infertility were documented and the overall prevalence of infertility was 4.73% (95% CI: 3.94%-5.59%), among them 2.6% (95% CI: 2.4-3.8%) had primary and 2.1% (95% CI: 1.8-3.4%) had secondary infertility. In this study, infertility was significantly correlated with age (r=0.051, p=0.032), educational level (r=-0.41, p=0.001), body mass index (r=-0.012, p=0.018), waist circumference (r=0.027, p=0.022), history of abortion (r=0.099, p=0.026), and family history of infertility (r=0.121, p=0.001). Conclusion: The results of our study showed that the prevalence of infertility among women living in Yazd was lower compared to the other regions in Iran. Female factors were the main cause of infertility in central part of Iran.